POSSIBILITY OF APPLICATION OF CRYSTALHIDRADES OF COBALT CHLORIDE FOR DRYING TRANSFORMER OILS - D. M. Valiullina; V. K. Kozlov; G. I. Rizvanova (Известия высших учебных заведений: Проблемы энергетики, 2018)
This paper presents the results of experiments for studying the possibility of using crystalline cobalt chloride for drying of transformer oils. It is shown that the use of crystalline hydrates of cobalt chloride for the drying of transformer oils leads to their complete dehydration. This is due to the interaction between the molecules of cobalt chloride and water. To determine the interaction of cobalt chloride with oil and water, absorption spectra in the visible and near-IR region at room temperature were studied in cuvettes 10 mm thick in the wavelength range λ 300 ÷ 1000 nm. It is shown that, regardless of the amount of cobalt chloride added, the transformer oil spectra do not change and, consequently, the chemical composition of the oil does not change. Thisindicatesthatthe cobalt chloride does not react with the transformer oil and remains in full at the bottom of the container with transformer oil. This method is more economical and less "resource-intensive".